Evolution of Total Polyphenols Content and Antioxidant Activity in Broccoli Florets during Storage at Different Temperatures - Andrea Mahn; M. Paz Rubio (Journal of Food Quality)
Broccoli has great potential as functional food because of its high content of bioactive compounds. Polyphenols are to a great extent responsible for the high antioxidant activity of broccoli. An important challenge to keep the health promoting properties of broccoli is preservation, with freezing and refrigeration being the preferred methods. Despite storage at low temperature reduces the rate of deterioration reactions, some reactions still occur, thus affecting the content of bioactive compounds. In this work, we investigated the evolution of total polyphenols content and antioxidant activity in blanched and unprocessed broccoli florets during storage at different temperatures (−45°C to 20°C). Both antioxidant activity and total polyphenols content increased at the beginning of storage at −21, −1, 10, and 20°C, followed by a decrease. Storage at −45°C produced no significant variations. The uneven behavior of antioxidant activity precluded modeling. The evolution of polyphenols was well described by a two-consecutive-reaction model, with r≥0.86 and MSE ≤ 0.1. The Ea values obtained for polyphenols formation (27–32 kJ/mol) and degradation (26–38 kJ/mol) confirm that, in both unprocessed and blanched broccoli, the same reactions are responsible for the evolution of polyphenols content. Our results may contribute to design preservation strategies of broccoli.